LEADERSHIP QUESTION AND THE CHALLENGES OF COMMUNITY DEVELOPMENT IN NIGERIA - Iheriohanma, E. B. J.; Wokoma, Chiemela U.; Nwokorie, Chinedu N. (European Scientific Journal, ESJ, 2014)
It is disheartening that despite efforts and resources put in transforming the rural communities in Nigeria, they have continued to remain underdeveloped. Several approaches, among which is community development, have been adopted to improve the lives of the people, all to no avail. This paper on leadership question and the challenges of community development in Nigeria examines why these communities have continued to remain poor. The methodology adopted is analytical discussion of library materials. The paper examines what community development entails, and the leadership challenges that have undermined its effective roles in rural transformation and community development in Nigeria. It observes that leadership is fraught with many challenges that have impinged on its efforts at transforming the rural communities despite their abundant human and material resources. It looks at those factors that have blurred the visions of leadership in community development. The development of the resources could leap frog the communities as foundations for development of national economies and integration to global markets. Having examined the exigencies of genuine and critical knowledge leadership, the paper recommends among others, that leadership for community development be development-oriented, shun corruption, be transparent and accountable; development assistance agencies and government to re-examine the internal and external factors militating against rural transformation; and the structural policies of development to be re-evaluated to examine why they have not achieved targets.